2021
DOI: 10.1016/j.bioactmat.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Functionalizing DNA nanostructures with natural cationic amino acids

Abstract: Complexing self-assembled DNA nanostructures with various functional guest species is the key to unlocking new and exciting biomedical applications. Cationic guest species not only induce magnesium-free DNA to self-assemble into defined structures but also endow the final complex nanomaterials with new properties. Herein, we propose a novel strategy that employs naturally occurring cationic amino acids to induce DNA self-assembly into defined nanostructures. Natural l -arginine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Noncanonical self-assembly of DNA with guest molecules is a promising strategy to construct DNA nanostructures with new properties and subsequently extend their biomedical applications. For example, endogenous polyamines, [12] carbon quantum dots, [13] and amino acids [14] are capable of assembling DNA in a magnesium-free manner. Spermidine, a natural polyamine, has three positive charges and can interact with nucleic acids and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Noncanonical self-assembly of DNA with guest molecules is a promising strategy to construct DNA nanostructures with new properties and subsequently extend their biomedical applications. For example, endogenous polyamines, [12] carbon quantum dots, [13] and amino acids [14] are capable of assembling DNA in a magnesium-free manner. Spermidine, a natural polyamine, has three positive charges and can interact with nucleic acids and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Positive molecules and proteins [35] Molecular assembly Stimuli-responsive biosystem, bio-imaging Positively charged nanomaterials (gold nanoparticles, [172] and luminescent nanodots et al) [107] Photothermal and photodynamic effects, fluorescence properties Gene regulation, immunoassay, immunotherapies, advanced chemical therapy Lipids, [81] lipidoids, polymers [97] High uptake efficacy, endosomal escape, membrane fusion Chemical therapies, gene therapies, immunotherapies…”
Section: Electrostatic Adsorptionmentioning
confidence: 99%
“…It was demonstrated that cationic guest species not only resulted in the formation of DNA nanoarchitectures with defined structures but also induced the complex nanomaterials with emerging biological characteristics. [ 35 ] Similarly, spermidine could adjust the isothermal self‐assembly of DNA nanoprisms. In comparison to conventional Mg 2+ ‐assembled DNA nanoprisms, the spermidine‐DNA nanoprisms show higher thermal ability and enhanced resistance to enzymatic degradation.…”
Section: Interaction Between Nucleic Acids and Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that cationic amino acids such as arginine and lysine are capable of facilitating DNA self-assembly into defined nanostructures. 26 In another study, Markvoort et al revealed the counterion-dependent stabilization mechanisms by atomistic molecular simulation. 27 Oligolysines stabilize DNA by connecting adjacent DNA helices and preventing helix repulsion simultaneously.…”
Section: Biomaterials Science Papermentioning
confidence: 99%